OPTIMATION TEMPERATURE AND INCUBATION TIME SONICATION METHOD EXTRACTION PURITY AND CONCENTRATION OF Escherichia coli DNA - Syary Dewi Sundhary; Asep Iin Nur Indra; Acep Tantan Hadiana; Yogi Khoirul Abror (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Escherichia coli is a Gram-negative, facultative anaerobic bacterium naturally commonly found in the gastrointestinal tract, and can be identified through its DNA detection. However, to ensure the accuracy and purity of the sample, repeated testing is required so that the results demonstrate consistent stability. Purpose: This study aims to determine the optimum temperature and incubation time of the sonication extraction method and to increase the purity and concentration of E. coli DNA. Method: The method used was quasi-experimental. This study used samples of pure isolates of E. coli DNA from patients who were positive for gastrointestinal infections. Result: It was obtained that the concentration of E. coli DNA samples at 50⁰C for 10 minutes had the largest average of 87 ng/μL, compared to the concentration of E. coli DNA samples at 50⁰C for 20 minutes of 30.8 ng/μL.The purity of E. coli DNA samples at 30⁰C for 20 minutes has the greatest average of 1.9, compared to the purity of E. coli DNA samples at 60⁰C for 15 minutes by 1.6. The data obtained was then analyzed with Microsoft excel. Conclusion: The optimum incubation temperatures for the sonication extraction method are 30⁰C and 50⁰C, while the optimum incubation times for the sonication extraction method are 20 minutes and 10 minutes.